The Role of Local Communities in Responding to Health Crises and Disaster Mitigation: A Systematic Literature Review - Soalihin, Soalihin; Asmawi, Asmawi; Riyanto, Danang; Ariyani, Iin; Nur, Nur Hamdani; Sudiyasa, I Kadek (Media Publikasi Cendekia Indonesia, 2025)
Health crises and natural disasters increasingly threaten communities worldwide, exacerbated by urbanization, climate change, and the vulnerability of populations in high-risk areas. Urban poor communities, in particular, are at heightened risk, making robust frameworks for health impact assessments essential. Local communities, with their deep understanding of social, cultural, and geographic dynamics, play a crucial role in disaster and health crisis management. Their involvement enhances resilience, facilitates timely responses, and supports post-disaster recovery, as demonstrated during the COVID-19 pandemic and natural disasters like floods and earthquakes. Despite the significant potential of local communities, challenges such as limited resources, poor coordination, and insufficient policy support hinder their effectiveness. This Systematic Literature Review (SLR) explores the roles and contributions of local communities in responding to health crises and disasters, identifying successful strategies, key influencing factors, and gaps in the current research. The review emphasizes the importance of empowering local communities through effective training, resource management, and cross-sector collaboration. The findings provide valuable insights for policymakers and stakeholders, offering guidance on strengthening community involvement as an integral component of health crisis and disaster mitigation strategies. The active engagement of local communities, supported by government policies, education, and strong networks, is essential for building resilient societies capable of managing future health and environmental challenges.